2014
DOI: 10.1166/jnn.2014.10007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxygen Plasma Treatment on Carbon Nanotube-Based Sensors

Abstract: We present the research results of the use of plasma modification for the fabrication of carbon nanotube-based devices for chemical and biological sensing. The oxygen plasma treatment of multiwalled carbon nanotubes (MWCNTs) effectively grafts oxygen atoms onto the CNT surface. For investigating the impact of plasma modification on the MWCNT-based sensor performance, three different sensors are fabricated: NH3 gas sensors, humidity sensors, and immunosensors. The plasma-modified MWCNTs (p-MWCNTs) exhibit a sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…After each treatment, the oxidation/reduction currents peaks were enhanced. The values for oxidation current followed this trend: 8.16 × 10 −3 A for bare electrode, 1.03 × 10 −2 A for OP treated electrode, 1.50 × 10 −2 A for spray deposited SWCNTs on OP treated electrode, and 1.96 × 10 −2 A for OP treated SWCNTs on OP treated Besides the higher current generation, the OP treatment leads to the formation of carbonyl and/or carboxylic groups, as reported in the literature [28]. The presence of these groups can improve the immobilization of antibodies on the surface of SWCNTs.…”
Section: Surface Characterization and Electrochemical Properties Of Hsupporting
confidence: 79%
See 3 more Smart Citations
“…After each treatment, the oxidation/reduction currents peaks were enhanced. The values for oxidation current followed this trend: 8.16 × 10 −3 A for bare electrode, 1.03 × 10 −2 A for OP treated electrode, 1.50 × 10 −2 A for spray deposited SWCNTs on OP treated electrode, and 1.96 × 10 −2 A for OP treated SWCNTs on OP treated Besides the higher current generation, the OP treatment leads to the formation of carbonyl and/or carboxylic groups, as reported in the literature [28]. The presence of these groups can improve the immobilization of antibodies on the surface of SWCNTs.…”
Section: Surface Characterization and Electrochemical Properties Of Hsupporting
confidence: 79%
“…As shown in Figure 3a, increasing the OP power from 9 W to 24 W enhanced the oxidation/reduction current peaks reaching a maximum of 1.96 × 10 −2 A for an OP power of 24 W. This current enhancement can be related to a possible degradation of SDS from SWCNTs network. By further increasing OP power from 24 W to 39 W, the generation of oxidation/reduction current was reduced, potentially due to the chemical etching of SWCNTs at high power (as previously indicated by Ham et al 2014) [28], as well as due to the increase in defect density on the SWCNTs surface [34].…”
Section: Surface Characterization and Electrochemical Properties Of Hmentioning
confidence: 64%
See 2 more Smart Citations
“…Besides, the sensitivity and selectivity of carbon allotrope-based sensors can also be further enhanced by proper surface treatment or ion doping. In a work by Ham et al [226], it was reported that oxygen plasma treatment on CNTs improved the immuno-sensing detection limit by almost 1000 times when compared to the standard ELISA assay. On the other hand, non-treated CNTs exhibit no detectable signal.…”
Section: Future Outlookmentioning
confidence: 99%